2022
DOI: 10.3390/jcm11143987
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Potential Pathogenesis of Cardiac Necrotizing Enterocolitis in Neonates with Congenital Heart Disease: A Narrative Review

Abstract: Neonates with congenital heart disease (CHD) are at an increased risk of developing necrotizing enterocolitis (NEC), an acute inflammatory intestinal injury most commonly associated with preterm infants. The rarity of this complex disease, termed cardiac NEC, has resulted in a dearth of information on its pathophysiology. However, a higher incidence in term infants, effects on more distal regions of the intestine, and potentially a differential immune response may distinguish cardiac NEC as a distinct conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 118 publications
2
14
1
Order By: Relevance
“…We found that infants with higher exposure to HM feeding had lower odds of S1P preoperative and postoperative NEC. These findings are consistent with two decades of research in preterm populations, and are important in light of a 2022 review by Burge et al 43 outlining potential differences between NEC in preterm infants and the cardiac NEC experienced by infants with CHD. Burge and colleagues suggested that cardiac NEC is, in part, a function of impaired gut perfusion, with resulting hypoperfusion and mesenteric ischemia contributing to an endothelial inflammatory response with associated gut permeability and pathogenic translocation.…”
Section: Necrotizing Enterocolitissupporting
confidence: 84%
See 1 more Smart Citation
“…We found that infants with higher exposure to HM feeding had lower odds of S1P preoperative and postoperative NEC. These findings are consistent with two decades of research in preterm populations, and are important in light of a 2022 review by Burge et al 43 outlining potential differences between NEC in preterm infants and the cardiac NEC experienced by infants with CHD. Burge and colleagues suggested that cardiac NEC is, in part, a function of impaired gut perfusion, with resulting hypoperfusion and mesenteric ischemia contributing to an endothelial inflammatory response with associated gut permeability and pathogenic translocation.…”
Section: Necrotizing Enterocolitissupporting
confidence: 84%
“…Dysbiosis of the gut microbiome related to high systemic inflammation, 44 prophylactic antibiotics, and delayed enteral feeding are known to play a role in NEC and intestinal injury in neonates. 43 Despite potential differences in etiology between preterm and cardiac NEC, our findings suggest that the protective benefits of HM demonstrated for preterm infants extrapolate to the SV CHD population. Four recent systematic reviews and meta-analyses 16,16,24,26 demonstrate convincing reductions in preterm NEC due to provision of HM and/or avoidance of infant formula (eg, 68% reduced risk; 25 4% lower incidence 16 ).…”
Section: Necrotizing Enterocolitismentioning
confidence: 72%
“…Lastly, unless there is documented ventricular dysfunction by echocardiogram, inotropic infusions should not be utilized for the sole purpose of improving the cardiac function especially if the blood pressure is acceptable. Inappropriate overuse of inotropic infusions changes the circulation balance and compromise the systemic blood flow with potential serious consequences on the gut and kidneys perfusion [8,9].…”
Section: General Considerationsmentioning
confidence: 99%
“…Reperfusion may trigger the inflammatory cascade, damaging the mucosal barrier and allowing for invasion of pathogenic bacteria that contribute to the development of NEC. [100][101][102] Preterm infants fed formula have 6-10 times the risk of NEC compared with infants fed exclusively maternal HM. 103 Similarly, a large, retrospective cohort study (n = 546) found that infants with congenital heart disease receiving exclusive, unfortified HM before neonatal cardiac surgery were significantly less likely to develop NEC (odds ratio [OR] = 0.17; 95% CI, 0.04-0.84) than those receiving formula, fortified feeds, or no preoperative feeds.…”
Section: Infant Health Benefits Of Hm Provision Immune and Gastrointe...mentioning
confidence: 99%
“…Infants in a postoperative state or with other conditions resulting in hypoperfusion to the gastrointestinal tract, such as congenital heart disease (CHD) (up to 9% prevalence of NEC for single‐ventricle physiology), are also at risk for NEC as blood is shunted away from the intestines and toward critical organs for survival, potentially leading to hypoxic ischemic injury. Reperfusion may trigger the inflammatory cascade, damaging the mucosal barrier and allowing for invasion of pathogenic bacteria that contribute to the development of NEC 100–102 . Preterm infants fed formula have 6–10 times the risk of NEC compared with infants fed exclusively maternal HM 103 .…”
Section: Infant Health Benefits Of Hm Provisionmentioning
confidence: 99%